Case Report: Early-Onset Guillain–Barre Syndrome Mimicking Stroke - Sun, Jing; Gao, Yu; Chi, Lumei; Cao, Qingyang; Ning, Zhijie; Nan, Guangxian (Frontiers in Neurology, 2021)
Introduction: Guillain-Barre syndrome (GBS) is an acute immune-mediated inflammatory demyelinating polyneuropathy characterized by symmetrical limb weakness and areflexia. GBS can have different clinical manifestations; hence, the initial symptoms are also varied. Here, we describe a rare case of GBS presenting as hemiparesis and cranial nerve palsy, which mimic brainstem stroke. Case presentation: A 53-year-old man was admitted to the hospital with a 3-hour history of left arm weakness, glossolalia, and right eyelid droop. After admission, his condition suddenly worsened, with quadriplegia, bilateral peripheral facial palsy, bilateral ophthalmoplegia and other neurological symptoms. Based on the findings from a neurological examination, magnetic resonance imaging, cerebrospinal fluid analysis and nerve conduction study, a diagnosis of GBS was made. He received intravenous immunoglobulin (0.4 kg/day) for 5 days. After 20 days of systematic therapy, his dysphagia, dyspnea, facial paralysis, ocular movement disorder and leg weakness recovered almost completely, but his arms were still moderately impaired, with a power of 4/5. Fortunately, the patient recovered well without any sequelae after 2 years of follow-up. Conclusions: In patients with an atypical presentation, the diagnosis of GBS is often delayed. With this case report, we intend to highlight the fact that some symptoms mimicking stroke may be a feature of Guillain-Barre syndrome at onset; close observation and timely diagnosis are crucial for clinicians. Neuroimaging is a valuable diagnostic tool in differentiating stroke from GBS.